Sedentary Lifestyle and Prospective Health Risks: A Pilot Study Among Bangladeshi Corporate Professionals (Bangladesh Pharmaceutical Journal, 2024)
Physical inactivity is one of the global health problems due to increased automation, moving less than before causing people to an elevated risk of developing various health conditions like obesity, hypertension, heart disease, etc. Most of the aforementioned diseases are linked to unhealthy lifestyles that are quite preventable. Although very few studies have been done related with sedentary lifestyle and its risks in Bangladesh, no study was focused on corporate professionals whom are at high health risk due to their job nature. This study therefore aims to explore the sedentary lifestyle and associated health and lifestyle related factors that might play role in the worsening of healthy life. Results of our study concluded that professionals belonging to age group between 25-29 years are most likely heading towards the risk zone of developing sedentary lifestyle associated risk according to WHO guidelines on sedentary lifestyle especially high body mass index (BMI 25 and more). Among the studied participants 78% were smokers and 21% were alcoholics. Moreover, 63% corporates reported that they could sleep 6 hour or less in a day, while 64% of the participants claimed that their stress level is high (7 to 10) in a 10 scale. Almost one fourth (24%) of the participants informed that they did not do any format of physical activity, and 26% participants were working for 5 years or more. Our data adequately pointed out some leading risk factors among the corporates that directly or indirectly provoke prospective health risks as described in numerous number of previous studies.Bangladesh Pharmaceutical Journal 27(1): 73-84, 2024 (January)